2020
DOI: 10.3390/ijerph17197263
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Literacy Intervention on Help-Seeking in Athletes: A Systematic Review

Abstract: Mental health literacy (MHL) is recognised as a major factor in whether athletes seek help when they experience mental health difficulties. Therefore, the current study aimed to provide a systematic review of the effectiveness of MHL training programmes in improving mental health knowledge and help-seeking and reducing stigma among athletes. To identify intervention studies of MHL programmes, five electronic databases were systematically searched for articles published before May 2020. The selection procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…The study also acknowledged the role of mental health literacy in providing avenues to support service acquisition (Hurley et al, 2018 ). Similar international studies found comparable results (Bu et al, 2020 ; Hurley et al, 2021 ).…”
Section: Understanding Mental Health Context In Sportsupporting
confidence: 76%
“…The study also acknowledged the role of mental health literacy in providing avenues to support service acquisition (Hurley et al, 2018 ). Similar international studies found comparable results (Bu et al, 2020 ; Hurley et al, 2021 ).…”
Section: Understanding Mental Health Context In Sportsupporting
confidence: 76%
“…This situation causes serious concerns to mental health professionals as only one-third of those who experience mental disorders seek professional help [ 2 ]. Evidence suggests that individuals’ help-seeking attitudes can be enhanced with better mental health literacy [ 3 ]. In addition, anxiety and depression in young adults are linked with higher stress levels and poorer psychological well-being [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a null effect was found in help-seeking behaviours for both postintervention and follow-up intervention. 20 Therefore, the authors concluded that Mental Health Literacy interventions could enhance help-seeking attitudes and intentions and mental health knowledge and reduce stigma but do not increase help-seeking behaviours. 20 Another study suggested that in addition to sport-specific interventions for athletes, a better understanding of specific needs of the athlete and availability of good treatment may create a follow-on effect of increased help-seeking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…14 A recent systematic review based on five included studies (1239 participants in total) focused on the effectiveness of Mental Health Literacy training programmes in improving mental health knowledge and help-seeking and reducing stigma among athletes. 20 Overall, either small or medium effects were found for mental health knowledge, stigma reduction, help-seeking attitudes, and intentions for postintervention and follow-up intervention. In contrast, a null effect was found in help-seeking behaviours for both postintervention and follow-up intervention.…”
Section: Attitude Help-seeking Behaviours and Confidencementioning
confidence: 93%
See 1 more Smart Citation